A interface entre o Programa Nacional de Alimentação Escolar, os serviços de assistência técnica e extensão rural e a agricultura familiar, como processo educativo de acesso ao mercado no Estado de Minas Gerais - Pires, Ademar Moreira (2017)
The motivation of this research was based on the experience with the National School Feed-ing Program - PNAE in the Technical Assistance and Rural Extension Company of Minas Gerais - EMATER-MG, since 2009, and aims to discuss the PNAE interface with the services Technical Assistance and Rural Extension - ATER and family agriculture, as an educational process of access to the market. The research has as theoretical presuppositions, the ATER services, in the perspective of an emancipatory rural extension, of an educational and trans-formative character, aiming at the formation of skills and changes that allow the development of a social practice where the extensionists can act as mediators in the construction of knowledge for the construction of educational processes. As well as understanding the PNAE as an achievement of family farming as historical subjects and important producers and direct food suppliers, whose transformations have not broken the peasant tradition that strengthens their capacity to adapt to the new demands of society and in schools as a right to healthy eat-ing for students from the perspective of food re-education. For the analysis proposed, a case study was carried out in the city of Brumadinho, Minas Gerais, Brazil, through the history of PNAE implementation, an exploratory study with extension agents of EMATER-MG and the use of PNAE exploratory data in Minas Gerais and Brazil. Semi-structured questionnaires and documentary analysis were used as research techniques. This research challenge emerges from a simple and somewhat obvious proposal, but also involves an immense complexity, which in many cases, the implementation and perception of the PNAE has been reduced to a simple marketing channel where farmers deliver food and schools receive them, as if they were commoditized products. In addition to the opportunity to make a reflection on the pro-cess of buying food from family agriculture for school feeding, based on its principles and objectives, failing to take ownership of an educational process, even considering the participa-tion of technical assistance and extension rural, and the program is an achievement of family farming and implemented in the school environment. The results found in the present study demonstrate that the interface between the PNAE, ATER and family farming favors an educa-tional process of market access to farmers, rural extension and PNAE executors. This process was affirmed by 94% of respondents, for information on access to other marketing channels and the need to adopt new standards of production and marketing by family farmers, for the need to search for new knowledge regarding the process of production organization and commercialization in rural extension, as well as a greater understanding and approximation of family agriculture by the schools, a process based on the analysis and theoretical discussion of Gohn (2006), Gadotti (2012) and Freire (1983). The study also pointed to a growth in PNAE implementation since 2009, both in the municipality of the case study, as well as in Minas Gerais and Brazil. In Brumadinho, the increase in resources invested in the purchase of food from family farms was 85.34%, comparing the years from 2010 to 2015. It can be seen that municipalities were able to buy more than 70% of the value for the PNAE, arriving in some cases, to buy more than 100% of the value passed on to PNAE by the FNDE, as well as to identify municipalities in the State with "zero" execution of the purchase of food from family agriculture to the PNAE, even in 2014.